The Influence of Peers on Entrepreneurial Interests of Students of the Family Welfare Education Study Program Padang State University - Marisa Ulfa; Asmar Yulastri (Universitas Negeri Padang, 2023)
This study aims to: 1) Describe the peer level of students of the Family Welfare Education Study Program, Padang State University, 2) Describe the interest in entrepreneurship of students of the Family Welfare Education Study Program, Padang State University, and 3) Analyze the level of influence of peers on the interest in entrepreneurship of Study Program students Padang State University Family Welfare Education. This type of research is classified into a quantitative type with a correlational approach. The population in this study were students of the Family Welfare Education Concentration Study Program on Culinary and Fashion Design, namely the 2018 and 2019 Classes with a total of 333 people. The sample of this research is 77 people with the sampling technique is simple random sampling. Data collection techniques were carried out using a questionnaire (questionnaire) using a Likert scale that has been tested for validity and reliability.The results of this study are: 1) Peer influence of students of the Padang State University's Family Welfare Education Study Program is in the medium category, with a percentage of respondents' achievement levels of 77%. 2) The interest in entrepreneurship for students of the Family Welfare Education Study Program, Padang State University, is in the high category with a percentage of respondents' achievement rate of 84%. 3) Peers have a significant effect on the interest in entrepreneurship of students of the Family Welfare Education Study Program, Padang State University, which has a high influence of 58.3%.